Characterizations of thermoplastic starch and starch reinforced montmorillonite clay nanocomposite - Abdul Razak, Nur Humairah; Ahmad, Zuraida; Sarifuddin, Norshahida; Z.S., Naqiah (American-Eurasian Network for Scientific Information, 2014)
This paper reported the characterizations of thermoplastic starch (TPS) and starch/nanoclaycomposite prepared from sago (Metroxylonrottb.) and Montmorillonite (MMT) nanoclay. Preparation of nanocomposite using inorganic filler such as MMT is among the means to enhance some properties of starch biopolymer. The thermoplastic starch-Montmorillonite (TPS-MMT) nanocomposite was produced by plasticizing with glycerol through melt blending before being compression moulded. The investigated TPS and nanocomposite were prepared at starch/glycerol weight fraction of 70:30 with 3, 6, and 12 wt % of MMT content. The degree of crystallinity of the TPS-MMT was analyzed by X-ray Diffraction (XRD) which showed that TPS crystalline structure was affected by MMT integration while both XRD and Fourier Transform Infrared Spectroscopy (FTIR) suggested the occurrence of matrix-reinforcement intercalation. Scanning Electron Microscope (SEM) presented micrographs of continuous phase and good adhesion of TPS-MMT nanocomposite at lower clay concentration